(untitled) (Journal of Management & Business, 2021)
The proposed article studies the conceptual foundations of cooperativism in the urban socialist transition, considering the contributions of different authors and the experience of this form of organization of production. In it, the situation of agricultural and non-agricultural cooperatives is analyzed, to be able to define a group of positive and negative experiences that favor the development of the territory of Cienfuegos. As an essential result, the potentialities, and restrictions of cooperativism in this locality are identified. The investigation contributed to the conception and implementation of government strategies and policies related to local development; with the aim of increasing food production as a priority element of the national economy, promoting new employment routes and raising the quality of life of the population. This issue responds the Food Sovereignty Program (SAN) in Cuba, the 2030 Agenda and the Sustainable Development Goals for Latin America as a region, among other relevant documents.